Direct and indirect effects of additions of chromophoric dissolved organic matter on zooplankton during large‐scale mesocosm experiments in an oligotrophic lake. (12th August 2015) - Cooke, Sandra L.; Fischer, Janet M.; Kessler, Kirsten; Williamson, Craig E.; Sanders, Robert W.; Morris, Donald P.; Porter, Jason A.; Jeffrey, Wade H.; DeVaul Princiotta, S.; Dean Pakulski, J.
Summary The effects of changes in chromophoric dissolved organic matter (CDOM) on zooplankton grazers in pelagic food webs can be difficult to predict due to the potential for conflicting direct and indirect effects of CDOM on water column optics and food‐web dynamics. We compared the responses of two dominant zooplankton groups, Daphnia spp. and calanoid copepods, to elevated CDOM in two mesocosm experiments conducted in a transparent, oligotrophic lake. In the first experiment, low, medium and high additions of CDOM [dissolved organic carbon (DOC) = 2.7, 3.0 and 4.3 mg L−1, respectively] and non‐manipulated controls (DOC = 1.6 mg L−1) were used to test the hypothesis that food‐web stimulation will increase with CDOM concentration. In the second experiment, we manipulated both CDOM (control and addition) and ultraviolet radiation (UV; ambient and shielded) to determine the importance of CDOM as a UV screen, as well as to examine the role of UV in food‐web stimulation by CDOM. We also conducted short‐term bioassays alongside this second experiment to assess the food resources for Daphnia and calanoids in treatments with UV‐exposed and non‐UV‐exposed CDOM. Daphnia abundance increased in the low and medium CDOM additions in the first experiment, and when food resources were simultaneously stimulated by CDOM and protected from the direct negative effects of UV in the second experiment. In contrast, calanoid copepod abundance declined or remained unchanged when CDOM was added, and this response was not mediated by food resources. Overall, our findings suggest that increased CDOM in clear lakes could alter the relative abundance of zooplankton groups through a combination of direct and indirect effects.